PENGEMBANGAN LAGU ANAK USIA DINI BERNUANSA MATEMATIKA UNTUK ANAK KELOMPOK B DI TK NEGERI PEMBINA TANJUNG BATU - rahmi fitria; Hasmalena hasmalena (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2018)
This development research aims to produce song of early childhood mathematical nuances. The development of early childhood song nuanced this using a combination of mathematical model development and evaluation of Rowntree Tessmer. Rowntree development model consists of three stages, namely the stage of planning, development and evaluation stage. At this stage of the evaluation performed formative evaluation expressed by Tessmer consists of five stages, i.e. the stage of self evaluation, expert review, one-to-one, small group evaluation evaluation and field test. Using data collection techniques of observation. Expert review results obtained average value results from experts on the song of early childhood mathematical nuances of 3,79 (very valid). Phase one to one evaluation obtained average results of observation on the song of early childhood mathematical nuances of 81% (both categories). Stages of small-group evaluaion obtained average results of observation on the song of early childhood mathematical nuances of 84% (both categories). In the field of observation values obtained at the test the song of early childhood mathematical nuances of 86% (both categories). Of all the stage that has been done then it can be inferred that the songs early childhood mathematical nuanced declared valid, practical, and have potential effects for the child.